+0  
 
0
118
2
avatar

what adds to -1 but multiplies to -60

Guest Mar 18, 2017

Best Answer 

 #2
avatar+79894 
+5

x + y  = -1      →  y = -1 - x     (1)

x*y   = - 60    (2)

 

Put (1) into (2)

 

x (-1 - x)  = -60

 

-x - x^2  = -60   multiply through by -1  and rearrange

 

x^2 + x - 60   =   0     solving for x   we have

 

 

x =  [ - 1 + sqrt(241)] / 2    and y   =  [ - 1 - sqrt(241)] / 2        or

 

x = [ - 1 - sqrt(241)] / 2     and  y  =  [ - 1 + sqrt(241)] / 2

 

 

cool cool cool

CPhill  Mar 18, 2017
Sort: 

2+0 Answers

 #1
avatar+5573 
+6

Technically, the two numbers are:

\(\frac{-1+\sqrt{241}}{2} \text{ . . .and. . . } \frac{-1-\sqrt{241}}{2}\)

 

I found just it by using the quadratic formula on this equation:

x2 - x - 60 = 0

 

There are no integers that add to -1 but multiply to -60.

 

Does your problem look like this:

x2 - x - 60 = 0

 

Or is there a number in front of the x2  ?

hectictar  Mar 18, 2017
edited by hectictar  Mar 18, 2017
 #2
avatar+79894 
+5
Best Answer

x + y  = -1      →  y = -1 - x     (1)

x*y   = - 60    (2)

 

Put (1) into (2)

 

x (-1 - x)  = -60

 

-x - x^2  = -60   multiply through by -1  and rearrange

 

x^2 + x - 60   =   0     solving for x   we have

 

 

x =  [ - 1 + sqrt(241)] / 2    and y   =  [ - 1 - sqrt(241)] / 2        or

 

x = [ - 1 - sqrt(241)] / 2     and  y  =  [ - 1 + sqrt(241)] / 2

 

 

cool cool cool

CPhill  Mar 18, 2017

7 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details